Ultrasound-guided percutaneous carpal tunnel release in patients on hemodialysis: early experiences and clinical outcomes - Wang PH; Li CL; Shao CJ; Wu KC; Chern TC; Jou IM (Dove Medical Press, 2019)
Ping-Hui Wang,1 Chia-Lung Li,2,3 Chung-Jung Shao,4 Kuo-Chen Wu,5 Tai-Chang Chern,6 I-Ming Jou7,81Department of Orthopedics, Chi-Mei Medical Center, Tainan 710, Taiwan; 2Department of Physical Therapy, College of Medicine, National Cheng Kung University, Tainan, 701, Taiwan; 3Department of Orthopedics, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan 704, Taiwan; 4Department of Orthopedics, Tainan Municipal Hospital, Tainan 709, Taiwan; 5Department of Orthopedics, Kuo General Hospital, Tainan, Taiwan; 6Chern Tai-Chang Orthopedic Clinic, Pingtung 900, Taiwan; 7Department of Orthopedics, E-Da Hospital, I-Shou University, Kaohsiung, Taiwan; 8Department of Orthopedics, National Cheng Kung University, Tainan, TaiwanPurpose: The purpose of the current study was to evaluate the effectiveness of ultrasound-guided percutaneous carpal tunnel release in hemodialysis patients with carpal tunnel syndrome.Methods: From February 2009 to April 2013, a prospective review of 113 consecutive cases of ultrasound-guided percutaneous carpal tunnel release was carried out in 84 hemodialysis patients. Results were analyzed by clinical subjective scale, two self-administered questionnaires, and functional evaluations at seven time points (1 week and 1, 3, 6, 12, 18, and 24 months).Results: Satisfactory symptom improvement in patients was 82%, 80%, 86%, 89%, 90%, 91%, and 90% at 1 week and 1, 3, 6, 12, 18, and 24 months postoperatively, respectively. Moderate pain was suffered in 11.5% of patients within 1 week, 8.8% within 1 month, 2.7% within 3 months, and none after 12 months postoperatively. Static two-point discrimination and Semmes–Weinstein monofilament examinations presented significant improvements after 1 week and 1 month postoperatively and with time. Postoperative grip power demonstrated recovery and a significant increase after 3 and 6 months postoperatively. Three-jaw chuck-pinch strength showed significant increase after 1 month postoperatively. There were no operative complications.Conclusion: Ultrasound-guided percutaneous carpal tunnel release is an effective and safe procedure in hemodialysis patients with carpal tunnel syndrome. The advantages include a less invasive procedure, no tourniquet needed, only limited infiltration anesthesia, minimal soft-tissue exploration, and relatively short operation time. Our data suggest this technique can reliably relieve clinical symptoms, with early restoration of grip and pinch strength.Keywords: carpal tunnel, hemodialysis, ultrasound, percutaneous release